Efficacy and safety of intravitreal injection of amikacin for endophthalmitis: a systematic review - ZiChao Ji; YUE XIE; XIN WANG; GUANGYAO LI; CHAO ZHANG (Polskie Towarzystwo Farmaceutyczne, 2023)
The aim of this study was to evaluate the efficacy and safety of intravitreal injection of amikacin in the treatment of endophthalmitis, and to provide reference for clinical decision making, registered (PROSPERO-CRD42022300395) and performed according PRISMA. PubMed, EMbase, The Cochrane Library, ClinicalTrials.gov, CNKI and Wanfang database were searched by computer to collect clinical studies on the efficacy and safety of intravitreal amikacin in the treatment of endophthalmitis. The retrieval period is from database construction to June 20, 2022. Two evaluators independently screened the literature according to the inclusion and exclusion criteria, extracted the data and evaluated the quality. Then qualitative analysis was used to describe the results. Finally, 5 case series studies were included, and the disease was exogenous endophthalmitis. A total of 115 patients and 115 eyes were included, with 11 to 39 patients in each study, 36.84% to 85.71% males and 30.4 to 60.7 years old on average. Follow-up was 6 weeks to 12 months. The study intervention of intravitreal vancomycin and amikacin improved visual acuity after combined therapy. In the 5 studies included in this study, no intraocular or systemic systemic adverse reactions were reported for intravitreal injection of amikacin. It was found that patients with exogenous endophthalmitis, including after surgery or ocular trauma, intravitreal injection of amikacin in combination with vancomycin is recommended for empiric treatment. However, high-quality randomized controlled trials or cohort studies are needed to verify this.